2013
DOI: 10.1186/1465-9921-14-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of PPARγ in carbon nanotube-elicited granulomatous lung inflammation

Abstract: BackgroundAlthough granulomatous inflammation is a central feature of many disease processes, cellular mechanisms of granuloma formation and persistence are poorly understood. Carbon nanoparticles, which can be products of manufacture or the environment, have been associated with granulomatous disease. This paper utilizes a previously described carbon nanoparticle granuloma model to address the issue of whether peroxisome proliferator-activated receptor gamma (PPARγ), a nuclear transcription factor and negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
54
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(68 citation statements)
references
References 27 publications
(41 reference statements)
12
54
0
Order By: Relevance
“…Our previous studies noted that MWCNT-mediated granulomatous inflammation was exacerbated in mice with macrophage-specific PPARγ deficiency [22], therefore it was of interest to determine whether ESAT-6 effects were associated with reduced PPARγ expression. Results indicated that addition of ESAT-6 to MWCNT did not further reduce PPARγ mRNA expression in BAL cells (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous studies noted that MWCNT-mediated granulomatous inflammation was exacerbated in mice with macrophage-specific PPARγ deficiency [22], therefore it was of interest to determine whether ESAT-6 effects were associated with reduced PPARγ expression. Results indicated that addition of ESAT-6 to MWCNT did not further reduce PPARγ mRNA expression in BAL cells (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…C57BL/6J wild-type mice received an oropharyngeal instillation of MWCNT after sedation with isofluorane. MWCNTs (catalogue number 900–1501, lot GS1801, SES Research, Houston, TX) were freshly prepared and have been extensively described previously [10,22]. A single pulmonary instillation of MWCNT (100 μg) in PBS/35% surfactant (vehicle) ± ESAT-6 peptide 14 (NNALQNLARTISEAG) (20 μg) were delivered to wild-type C57Bl/6 mice.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…HP has been reported in metalworkers that were exposed to nontuberculous mycobacteria in contaminated metalworking fluid, providing an interesting example of a different pathogenic outcome from exposure to these organisms that results in a form of granulomatous inflammation in the lung [64]. Recent studies demonstrate that carbon nanotubes can induce some features of a sarcoidosis-like granulomatous reaction when injected into the lungs of mice, but fail to recapitulate the clinical features of sarcoidosis [65][66][67]. Whether the definition of sarcoidosis should include granulomatous responses in the lung induced by exposure to such known inorganic or organic agents remains a contested issue [68].…”
Section: Environmental Studies Of Sarcoidosis Etiologymentioning
confidence: 99%